Intraoperative tranexamic acid use in major spine surgery in adults: a multicentre, randomized, placebo-controlled trial†This Article is accompanied by Editorial Aew470. (March 2017) - Colomina, M.J.; Koo, M; Basora, M; Pizones, J; Mora, L; Bagó, J
Abstract: Background: Perioperative tranexamic acid (TXA) use can reduce bleeding and transfusion requirements in several types of surgery, but level I evidence proving its effectiveness in major spine surgery is lacking. This study was designed to investigate the hypothesis that TXA reduces perioperative blood loss and transfusion requirements in patients undergoing major spine procedures. Methods: We conducted a multicentre, prospective, randomized double-blind clinical trial, comparing TXA with placebo in posterior instrumented spine surgery. Efficacy was determined based on the total number of blood units transfused and the perioperative blood loss. Other variables such as the characteristics of surgery, length of hospital stay, and complications were also analysed. Results: Ninety-five patients undergoing posterior instrumented spine surgery (fusion of >3 segments) were enrolled and randomized: 44 received TXA (TXA group) and 51 received placebo (controls). The groups were comparable for duration of surgery, number of levels fused, and length of hospitalization. Transfusion was not required in 48% of subjects receiving TXA compared with 33% of controls ( P  = 0.05). Mean number of blood units transfused was 0.85 in the TXA group and 1.42 with placebo ( P  = 0.06). TXA resulted in a significant decrease in intraoperative bleeding ( P  = 0.01) and total bleeding ( P  = 0.01) relative to placebo. The incidence of adverse events was similar in the two groups. Conclusions: TXA did not significantly reduce transfusion requirements, but significantly reduced perioperative blood loss in adults undergoing major spinal surgery. Clinical trial registration: NCT01136590.